Great customer service on the telephone - Anderson, Kristin, 1962- (WorkSmart series., 1992)
First impressions are often lasting impressions. How customers are treated on the phone can quickly turn them into either an ex-customer or a customer for life. This thorough, quick-reading guide shows anyone who uses the phone -- from salesperson to manager to secretary -- how to treat it as a service tool that directly impacts on company profits. Readers will be able to double their effectiveness when they learn how to: * handle irate customers * end those ""endless"" calls * take meaningful messages * handle conference calls and transfer calls * screen calls and ask focused questions * use the phone during emergencies * improve their voice effectiveness With worksheets, checklists, and fill-in forms, this desktop primer will inspire fabulous phone service